Joint technological changes in multiple industries - Georg Quaas (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2025)
Most neo-Ricardian studies on the "choice of technique" are based on a comparison of alternative technologies applicable to the same industrial branch. Some authors even recommend restrict analyses of the long-run technological changes to a single industry. In reality, innovations often require technological changes in several industries. In this article, it is shown that a step-by-step analysis of complex technological innovations is path-dependent and does not always lead to a result. Furthermore: The number of mathematically possible switch-points is reduced by the number of affected industries and by ambiguous price relations in the vicinity of intersection-points of wage curves. This could, without simplification of Sraffa's theory, explain why situations in which two alternative technologies generate the same prices, i.e. switch-points, are empirically extremely rare events.
Keywords: B24; C67; O14; 330; capital theory; switch-points; choice of technologies; path-dependency; embedded equations